Interlinking Germany's global health strategy at the European level: An analysis of priorities and coordination potentials in EU partner countries - Michael Bayerlein (Stiftung Wissenschaft und Politik (SWP), 2024)
The German global health strategy review process offers the opportunity to place a stronger focus on the horizontal integration of Germany's global health efforts with those of European partners. This is urgently needed as the German strategy makes little reference to the European Union (EU) and entirely excludes EU member states. However, Germany's consideration of the strategic priorities of these actors would enable it to proceed in a united, coherent manner and to form new partnerships in specific policy areas. The systematic analysis of the strategies of other EU countries provides starting points for these considerations, as the identification of country-specific strategic priorities can shed light on opportunities for better linkages and coordination with the global health policies of other EU member states. Based on this, the partners that are particularly relevant for Germany in specific fields of action can be determined, and blind spots in German global health policy can be identified.
Keywords: 320; Germany; Global Health Strategy; European Union (EU); EU partner countries; priorities; coordination; World Health Organization (WHO)